Influence of conspecifics and road noise on the properties of the advertisement call of Phyllodytes luteolus (Anura, Hylidae) - Leonardo Marques de Abreu; Vinicius Guerra; Mirco Solé (Ecology and Evolution, 2024)
Abstract Acoustic communication in animals can be affected by multiple biotic (intra and interspecific) and abiotic (e.g., wind and rain) natural noises. In addition, human beings produce additional novel sources of noise, which can reduce or inhibit the reception of acoustic signals by conspecifics, leading to behavioral changes. In this study, we investigated whether sound of conspecifics and road noise additively affect the acoustic parameters of the advertisement call of males of a Yellow Heart‐tongued Frog (Phyllodytes luteolus). We hypothesized that males that vocalize in choruses (males calling nearby) and in areas close to highways (anthropic noise) will increase their temporal and spectral acoustic parameters, respectively, to avoid acoustic signal masking. We recorded the vocalizations of 38 males in environments close (N = 18) to and distant (N = 20) from highways in different social contexts (many or few individuals calling nearby). Contrary to our expectation, the results indicated that males calling in areas close to highways had lower dominant frequency calls than those from natural areas (far from highways), and that the density of males in the chorus had no influence on the acoustic parameters. Furthermore, we found a positive relationship between body size and intensity, indicating that larger individuals can emit calls that can reach greater distances. The advertisement call of Phyllodytes luteolus has a high dominant frequency, with little overlap with the frequency of anthropic noises (roads), which may explain its presence and reproductive success of this species in bromeliads from urbanized areas.